Evaluation of comprehensive spa treatment of osteoarthritis of the knee at the “Włókniarz” Sanatorium in Busko-Zdrój - Legwant, Zdzisław; Gawęda, Józef; Legwant-Wójcicka, Małgorzata; Kornecki, Wojciech (Medical Studies/Studia Medyczne, 2013)
Aim of the research : Evaluation studies have been carried out of the effectiveness of rehabilitation procedures with balneotherapy in osteoarthritis of the knee (OAK). Material and methods: Sulphide and hydrogen-sulphide salt waters, and kinesitherapy and chosen physiotherapy methods were used in treatment. Sixty-five people with osteoarthritis of the knee, with an average period of 20 years of duration of the disease, took part in the studies. These patients were divided into two groups. In the first group, baths in sulphide and hydrogen-sulphide salt waters with physiotherapy treatment were used. In the second group, analogous physiotherapy treatment was used, however, due to medical contraindications, sulphide baths were not used. Results : In both groups, a significant improvement of knee joint functions, alleviation of pain and improvement of endurance and aesthetics of walking were observed. Slightly better effects were observed in patients using baths in sulphide and hydrogen-sulphide salt waters. Conclusions: In view of the achieved improvement of the clinical state in patients with OAK, this form of comprehensive sanatorium rehabilitation is recommendable.